Design theory and methods using CAD/CAE - Chang, Kuang-Hua 1960- (The computer aided engineering design series, 2015)
The fourth book of a four-part series, Design Theory and Methods using CAD/CAE integrates discussion of modern engineering design principles, advanced design tools, and industrial design practices throughout the design process. This is the first book to integrate discussion of computer design tools throughout the design process.--Provided by publisher.